Banxia baizhu tianma decoction, a Chinese herbal formula, for hypertension: Integrating meta-analysis and network pharmacology - Lin, Jianguo; Wang, Qingqing; Xu, Siyu; Zhou, Simin; Zhong, Dongsheng; Tan, Meng; Zhang, Xiaoxiao; Yao, Kuiwu (Frontiers in Pharmacology, 2022)
Hypertension is a major cardiovascular risk factor, which seriously affects the quality of life of patients. Banxia Baizhu Tianma Decoction (BXD) is a Chinese herbal formula that is widely used to treat hypertension in China. This study aimed to evaluate the efficacy and potential mechanism of BXD for hypertension by meta-analysis and network pharmacology. Meta-analysis was performed to explore the efficacy and safety of BXD combined with conventional treatment for hypertension. Network pharmacology was used to explore the molecular mechanism of BXD in antihypertension. A total of 23 studies involving 2041 patients were included. Meta-analysis indicated that compared with conventional treatment, combined BXD treatment was beneficial to improve clinical efficacy rate, blood pressure, blood lipids, homocysteine, endothelial function, inflammation, and traditional Chinese medicine symptom score. In addition, meta-analysis indicated that BXD is safe and has no obvious adverse reactions. Network pharmacology showed that the antihypertensive targets of BXD may be AKT1, NOS3, ACE, and PPARG. The antihypertensive active ingredients of BXD may be naringenin, poricoic acid C, eburicoic acid, and licochalcone B. Due to the poor methodological quality of the Chinese studies and the small sample size of most, the analysis of this study may have been affected by bias. Therefore, the efficacy and safety of BXD for hypertension still need to be further verified by high-quality clinical studies.